Fintech Mempengaruhi Manajemen Keuangan? - Arief Rizqi; Hengki Vieri Panogari Vincentius Simarma; Mohamad Hanafi; Wildan Hilmi; Mira Nurfitriya (Eqien - Jurnal Ekonomi dan Bisnis, 2023)
Purpose — The background of this research journal is the development of the era where technology has changed human life behavior which has positive and negative impacts. So that the development of this era changes the behavior or habits of financial management that never existed in human civilization before. The purpose of this study was to determine the effect of fintech on the financial management of Entrepreneurship Study Program students at the Universitas Pendidikan Indonesia.Design/methodology/approach — This study uses a quantitative research method. The technique used in this research is a data collection technique in the form of a questionnaire (questionnaire).Findings — The hypothesis in this study is that there is a significant influence between Fintech (x) and financial management (y).Practical implications — This study's results can help students increase fintech awareness about financial management. And the results of this research can be used as learning material for academics, students, the community, and other parties.Originality/value — This research was conducted based on data-based research found on college entrepreneurship students at the Universitas Pendidikan Indonesia so this research has research originality.Keywords — College student, Entrepreneurship, Financial Management, FintechPaper type — Research paper